Seroprevalence of antibodies against Neospora caninum in extensive cattle farming in three districts of Parinacochas, Ayacucho - Fernández Cevallos, Angela (2021)
The aim of this study was to determine the seroprevalence of antibodies against Neospora caninum in cattle under an extensive production system in the districts of Chumpi, Coracora and Pullo of the province of Parinacochas, Ayacucho. In total, 209 blood serum samples from bovines older than four months of age were collected. The samples were analyzed using the indirect ELISA technique with the IDEXX Neospora 2X Ab kit to detect antibodies against N. caninum. A corrected seroprevalence of 12.2 ± 4.4% was found with a significant association (p<0.05) for the origin variable. The district of Coracora presented the highest prevalence with 19.7 ± 7.5%.